PERCEPTION OF BLOOD DONATION AMONG PAKISTANI YOUTH - Maqsood Ahmed; Muhammad Saeed; Usman Waheed; Ather Mujtaba; Amir Hanif; Anum Khalid; Farhan Rasheed (Pakistan Armed Forces Medical Journal, 2020)
Objective: To explore the factors which motivate or hamper our youngsters for blood donation and to understand the behavior of youth regarding blood donation through which we can rise voluntary blood donation.